The Optimization of Ethanol Production from Oil Palm Empty Fruit Bunches Hydrolysate by Using a Statistical Experimental Design - Choojit, Saovanee; Chansiriphota, Supattra; Phiboon, Kummarin (International Journal of Integrated Engineering, 2020)
The oil palm empty fruit bunch (OPEFB) is one of the potential lignocellulosic biomasses for ethanol production. In this study, ethanol production from OPEFB was investigated. Firstly, OPEFB was alkali-pretreatment with 15% (w/v) NaOH at 121˚C for 45 min and it provided of 67.2% cellulose, 22.8% hemicellulose and 7.2% lignin. The cellulose content in the alkali-pretreated OPEFB had increased 39.4% from untreated OPEFB, while the hemicellulose and lignin had decreased to 33.1% and 36.7% respectively. Secondly, alkali-pretreated OPEFB was hydrolyzed with 7% (v/v) H2SO4 at 140°C for 90 min. The highest glucose yield of 92.38% was obtained representing 55.54 g/L. Lastly, the glucose resulting was fermented to ethanol by Saccharomyces cerevisiae. A response surface methodology (RSM) with a central composite design (CCD) was applied in the experimental design to optimize the ethanol production condition. Four independent variables via initial glucose (55-85 g/L), pH (4.75-6.25), temperature (25-35ºC) and inoculum size (2.0-4.0%) were evaluated. A verification experiment indicated the optimal fermentation condition was as follows: 55 g/L initial glucose, pH 6.25, 2% inoculum size at 35±2ºC for 48 h. The highest ethanol yield of 40.76% (22.4 g/L, 0.41 g/g glucose) was over 80% of the theoretical ethanol yield produced from glucose fermentation, which was 28.05 g/L (0.51 g/g glucose). The ethanol yield achieved appears quite attractive and demonstrates that OPEFB have excellent potential resource of renewable energy. While the experimental design is useful for optimization designs with several variables and describing more complex behavior by including higher orders model components.